Comportamento suicida como fenômeno relacional: o impacto das tentativas de suicídio adolescentes nas dinâmicas e padrões relacionais familiares - Cacciacarro, Mariana Filippini (2023)
For each completed suicide there are about 20 attempts, which affects a significant contingent of families. Family theories can offer a new perspective of conceptualization about suicidal behavior. The systemic perspective allows us to understand suicidal behavior from a relational point of view, highlighting inter-relational patterns that can contribute to the maintenance of crises or contribute to the strengthening of family resilience and recovery. To identify and understand the impacts of suicidal behavior on family dynamics crossed by the threat of suicide, we developed a qualitative study based on grounded theory whose data were collected in focus groups conducted with family members with different degrees of kinship with adolescents with suicidal behavior. Suicide is still a big taboo in contemporary society, contributing to the maintenance of pejorative and stigmatizing meanings, besides hindering the construction of open dialogues on the subject, impacting the quantity and quality of available information. Among the demands and needs highlighted by the participants are the absence of clear information and precise orientations on how to manage suicidal crises, in addition to the difficulty in building a professional support network that is capable and available to welcome and guide the family. The coping strategies adopted by the family system can either favor the strengthening of the family resilience and its recovery process, or get it imprisoned in relational patterns based on the illness, feeding back the crises. Familybased interventions propose an expanded look at the complexity of suicidal behavior, facilitating the promotion of dialogues on the subject, as well as helping the family to face crises and to build second-order changes. We have developed, therefore, a systemic intervention tool focused on strengthening family resilience and encouraging their recovery process. The Family Help Plan is based on inviting dialogue and strengthening family bonds through four steps: identifying crisis situations; building plans and safety measures, encouraging dialogue, validation and embracement followed by building support networks. New studies are needed to validate the effectiveness of the Family Help Plan as a coadjutant strategy in the treatment of individuals with suicidal behavior in different care settings